2001
DOI: 10.1074/jbc.m009432200
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6*6, a Novel Polymorphism in Cytochrome P450 2A6, Has a Single Amino Acid Substitution (R128Q) That Inactivates Enzymatic Activity

Abstract: By using the polymerase chain reaction technique combined with restriction enzyme fragment length polymorphism (PCR-RFLP), a novel polymorphism of CYP2A6, CYP2A6*6, was detected in 0.4% of the Japanese population. To study the enzymatic properties of the CYP2A6.6 protein with a single amino acid substitution of arginine 128 to glutamine, both this isozyme and the CYP2A6.1 protein (wild-type) were produced in insect cells using a baculovirus system. Coumarin 7-hydroxylation, which reflects CYP2A6 activity, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…However, polymorphisms in genes have been shown to alter enzymatic activity, and in certain cases, the variant results in a reduction in activity (22). Polymorphic variants may thus play a mechanistic role by which COMT activity is reduced and result in the accumulation of mutagenic catechol compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polymorphisms in genes have been shown to alter enzymatic activity, and in certain cases, the variant results in a reduction in activity (22). Polymorphic variants may thus play a mechanistic role by which COMT activity is reduced and result in the accumulation of mutagenic catechol compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CYP2A6 and CYP2D6, the altered base causes a reduction in enzyme function (22,23). On the contrary, the variant form of the protein causes the enhanced activity of CYP1A1 and CYP1B1 enzymes (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Large interindividual variability in the cotinine formation has been demonstrated. [11][12][13][14][15] The half-lives of nicotine and cotinine after smoking are approximately 2 hr and 20 hr, respectively. 16) Because of the longer half-life of cotinine, it is generally used as a biomarker of smoking.…”
Section: Interindividual Dišerences In Cotinine Formation Andmentioning
confidence: 99%
“…CYP2A6*4 allele, in which the entire CYP2A6 gene is deleted, completely lacks the enzymatic activity. [20][21][22] Alleles possessing a single nucleotide polymorphism (SNP), such as CYP2A6*2 (L160H), 23) CYP2A6*5 (G479V), 24) CYP2A6 * 6 (R128Q), 14) CYP2A6 * 7 (I471T), 25) CYP2A6*9 (T-48G in TATA box), 26) CYP2A6*10, 15,27) and CYP2A6*11 (S224P), 28) have been reported to lead to decreased enzymatic activity in vitro and W or in vivo. In our studies, the relationship between the interindividual diŠerences in nicotine metabolism to cotinine and genetic polymorphisms of the CYP2A6 gene in Japanese and Korean subjects was determined.…”
Section: Interindividual Dišerences In Cotinine Formation Andmentioning
confidence: 99%
“…Polymorphisms of CYP2A6 that might affect enzymatic activity (Ariyoshi et al 2001;Kitagawa et al 2001;Pitarque et al 2001;Daigo et al 2002;Oscarson et al 2002;Xu et al 2002) or susceptibility to lung cancer (Pianezza et al 1998;London et al 1999;Miyamoto et al 1999) have been reported. However, some of those variants may be rare substitutions or limited to specific ethnic groups (Kitagawa et al 2001;Oscarson et al 1999Oscarson et al , 2002Xu et al 2002).…”
Section: Introductionmentioning
confidence: 99%